What is an atypical BSE? - Alessi, Antonio C. [UNESP] (My University, 2013)
The number of cases of Bovine Spongiform Encephalopathy (BSE) in the United Kingdom (UK) and Europe has decreased during the last years. The disease is designated as Classical BSE (C-BSE) once the prion protein involved is very constant and has genetic identity. On the other hand, atypical cases have occurred in several countries, apparently without any relationship with contaminated feeding. Atypical cases, H or L-BSE can have involvement with the etiology of the known C-BSE, first diagnosed in the UK. With the control of C-BSE based on rigid control of feeding, the occurrence of atypical BSE may predominate in the future. In this hypothesis atypical BSE, probably a spontaneous encephalopathy of cattle, will be considered as Sporadic BSE in contrast with the C-BSE that could be nominated UK-BSE.
Keywords: Atypical BSE; Bovine Spongiform Encephalopathy; BSE; Cattle; Prion protein